Corruption affecting small businesses in formal and informal districts of Cairo before & after the January 2011 Revolution - Fayed, Ahmed (AUC Knowledge Fountain, 2013)
Following the Arab Spring and specifically the January 25th 2011 revolution in Egypt, countries in the region continue to face turmoil economically, politically and at the security level. This has lead to great controversy and polarization between the different actors, and stagnation of the democratic transformation of the country. When looking at one of the root causes of the uprisings, corruption is specifically highlighted. Post-revolutionary governments have pledged to combat the phenomenon at all levels, but their policy impact is yet to be seen. The purpose of this research was to look at the types of corruption affecting small businesses in formal and informal districts of Cairo before and after the January 2011 revolution. The district of Nasr City was chosen, including its formal neighborhoods and the informal area of Ezbet Al-Haggana Small grocery businesses were selected as representatives of the largest business sector in Egypt. The purpose was to identify the discrepancies between the two types of sectors in the types of corruption they face on a daily basis, and how they have been impacted by the Revolution. This would allow us to gain insights on the barriers to conducting business after the Revolution and how anti-corruption policies affect businesses at the local level. The study findings indicate that corruption affecting small businesses in both formal and informal districts of Cairo decreased drastically, compared to before the revolution; the main reason for the results being the breakdown of citizens’ fears and the weakening of governmental power and authority, particularly in the police.